Implementation of Learning from the Book of Fadilah Amal in the Formation of Morals in Santriwati at the Ta'mirul Islam Islamic Boarding School, Surakarta - Rutasana, Fikri Nahdliyah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Students' morals will be formed according to what is taught by parents or closest family members, but often the good morals that have been formed within students can be damaged due to influences from the external environment, so school is the second place for forming good morals for students. This research aims to analyze the process of moral formation through learning the Book of Fadilah Amal in Islamic boarding schools. The research method uses a case study. Data collected through interview observation and documentation. The principal and teacher/homeroom teacher as research subjects. The results obtained from the research stated that students had followed the learning of the Book of Fadhilah Amal, but there were some students who did not behave well towards their surroundings, because during the learning process they joked a lot, came late and did not practice what had been taught by the teacher. Teachers must be more assertive in teaching and students must be more focused during the fadhilah Amal learning process so that what the school and teachers aspire to is achieved.